Preparation method of formaldehyde removal paper
By doping nanoscale OMS-2 molecular sieve into activated carbon fiber and loading metallic silver, an efficient formaldehyde degradation catalyst is prepared and embedded in the pulp, which solves the problem of reduced physical properties of existing aldehyde-removing wallpapers. Efficient formaldehyde removal and good physical properties are achieved.
Patent Information
- Application Number
- CN202411784876.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-21
AI Technical Summary
After adding high-efficiency formaldehyde adsorption and degradation catalysts, the physical properties such as softness and smoothness are significantly reduced, limiting their application in the high-end decoration field.
Nanoscale OMS-2 molecular sieve is doped into activated carbon fiber and loaded with metallic silver to prepare an efficient formaldehyde degradation catalyst and evenly embedded in the pulp.
It significantly improves the formaldehyde adsorption and degradation performance of the aldehyde removal paper, while maintaining the physical properties of the wallpaper, ensuring the continuous removal of formaldehyde in long-term use, and meeting the quality requirements in the high-end decoration field.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing paper, and in particular to a method for preparing formaldehyde-removing paper. Background Art
[0002] As people's requirements for indoor air quality continue to increase, wallpapers with formaldehyde adsorption and degradation functions, namely formaldehyde-removing wallpapers, have gradually become the focus of market attention. This type of wallpaper aims to effectively remove formaldehyde from indoor air by incorporating special components that have the function of adsorbing and degrading formaldehyde into its structure, thereby improving the living environment. Formaldehyde-removing wallpapers not only meet people's needs for beautiful decoration, but also show significant advantages in environmental protection and health.
[0003] In the preparation process of formaldehyde-removing wallpaper, the way of adding adsorbed and degradable components has a crucial impact on its performance. Traditional methods often directly adhere the adsorbed and degraded components to the wallpaper surface. Although this treatment method can achieve the adsorption and degradation of formaldehyde to a certain extent, its sustainability and stability are relatively poor. In order to overcome this defect, researchers began to try to add adsorbed and degraded components to the wallpaper slurry, so that the adsorbed and degraded components can be more evenly distributed in the internal structure of the wallpaper, thereby significantly improving the sustainability and stability of formaldehyde degradation. However, this method also faces the problem of low formaldehyde adsorption and degradation efficiency, and it is difficult to meet the needs of efficient formaldehyde removal.
[0004] In view of the problem of low formaldehyde adsorption degradation efficiency, the prior art CN111266129B proposes a new solution. This technology prepares an efficient formaldehyde adsorption degradation catalyst by loading Ag onto the OMS-2 molecular sieve. This catalyst shows excellent performance in formaldehyde degradation, which provides a possibility for improving the efficiency of formaldehyde-removing wallpaper. However, when the applicant tried to add this efficient catalyst to the papermaking pulp to prepare formaldehyde-removing wallpaper, new problems were encountered. Specifically, the addition of the catalyst has a negative impact on the physical properties of the wallpaper, resulting in a significant decrease in the softness and smoothness of the wallpaper, which to a certain extent limits its application in the field of high-end decoration. Therefore, how to ensure that the physical properties of the wallpaper are not damaged while maintaining efficient formaldehyde degradation performance has become a key issue that needs to be urgently solved in the current formaldehyde-removing wallpaper preparation technology. Summary of the invention
[0005] In view of the above problems, the present invention dopes OMS-2 molecular sieve into activated carbon fiber and loads metallic silver, thereby improving the formaldehyde adsorption and degradation performance of the wallpaper while ensuring the physical properties of the wallpaper.
[0006] Specifically, the present invention provides a method for preparing formaldehyde-removing paper, which comprises the following steps in sequence: (1) Nano-scale OMS-2 molecular sieves were doped into activated carbon fiber raw materials through wet mixing and ultrasound-assisted technology to form raw fiber doped with molecular sieves; (2) carbonizing the raw fiber doped with the molecular sieve to prepare activated carbon fiber containing the OMS-2 molecular sieve; (3) silver loading treatment is performed on the activated carbon fiber to obtain a formaldehyde degradation catalyst loaded with silver on the surface; (4) Add formaldehyde degradation catalyst to pulp and prepare formaldehyde-free paper through papermaking process.
[0007] Specifically, the nano-scale OMS-2 molecular sieve in step (1) has a particle size range of 5-50 nanometers and is doped into the activated carbon fiber raw material at a mass ratio of 5%-20%; the specific surface area of the activated carbon fiber raw material is 500-1500 square meters / gram.
[0008] Specifically, in the wet mixing and ultrasonic-assisted treatment in step (1), the frequency range of the ultrasonic treatment is 20-60 kHz, and the treatment time ranges from 30 minutes to 1.5 hours.
[0009] Specifically, the carbonization treatment in step (2) is carried out in a nitrogen atmosphere, the carbonization temperature ranges from 700 to 900° C., and the carbonization time ranges from 1 to 3 hours.
[0010] Specifically, the silver loading treatment in step (3) includes: immersing the activated carbon fiber in an aqueous solution containing a silver active component at a concentration of 0.05-0.2 mol / L, the immersion time ranges from 12 to 36 hours, the aging time ranges from 6 to 24 hours, and then drying at 80 to 120° C., and finally calcining at 250 to 350° C., and the calcination time ranges from 1 to 3 hours.
[0011] Specifically, the aqueous solution containing the silver active component is one of silver nitrate, silver phosphate, silver carbonate or silver acetate.
[0012] Specifically, the pulp in step (4) is prepared by mixing kraft softwood pulp and bleached kraft hardwood pulp in a mass ratio of 1:1 to 1:3; and the formaldehyde degradation catalyst is added to the pulp in a mass ratio of 1% to 10%.
[0013] Specifically, the papermaking process in step (4) includes: forming paper sheets by a wet papermaking process using a slurry containing a degradation catalyst; pressing the paper sheets at a pressure range of 1-3 MPa; drying the paper sheets at a temperature range of 90-110° C. for a time range of 5-15 minutes; applying a sizing agent using a polyvinyl alcohol or sodium carboxymethyl cellulose glue in an amount of 3%-7% of the paper weight; applying a non-woven fabric, the mass of the non-woven fabric being in a range of 5%-15% of the paper weight; and finally calendering the paper sheets at a pressure range of 0.5-1.5 MPa and 1-3 calendering times.
[0014] Specifically, the method further comprises printing a pattern on the formaldehyde-removing paper after the papermaking process in step (4), wherein the printing method includes gravure printing, flexographic printing or digital printing.
[0015] Specifically, the thickness of the prepared formaldehyde-removing paper product is 0.1-0.5 mm, and the gram weight ranges from 80-200 g / m2.
[0016] Compared with the prior art, the present invention has the following beneficial effects: First, the present invention prepares a highly efficient formaldehyde degradation catalyst by doping nano-scale OMS-2 molecular sieves into activated carbon fiber raw materials and loading metallic silver, which not only significantly improves the formaldehyde adsorption and degradation performance of the formaldehyde-removing paper, but also ensures the continuity and stability of formaldehyde degradation by evenly embedding it into the pulp. Compared with the traditional method of directly adhering the adsorbed degradation components to the surface of wallpaper, the formaldehyde-removing paper prepared by the present invention can more effectively remove formaldehyde from indoor air in long-term use, providing residents with a healthier and more environmentally friendly living environment.
[0017] Secondly, the present invention ensures that the physical properties of the formaldehyde-free paper are not damaged while maintaining efficient formaldehyde degradation performance. By combining the OMS-2 molecular sieve with the raw material fiber, and undergoing fine carbonization treatment and silver loading treatment, the obtained formaldehyde degradation catalyst will not have a negative impact on the physical properties such as the softness and smoothness of the paper after being added to the pulp. This makes the formaldehyde-free paper prepared by the present invention not only have excellent environmental performance, but also maintain a good decorative effect and user experience, meeting the high requirements for wallpaper quality in the high-end decoration field.
[0018] Finally, the preparation method of the present invention is simple and feasible, and is easy to industrialize. Through a series of steps such as wet mixing and ultrasonic assisted technology, carbonization treatment, silver loading treatment and papermaking process, formaldehyde-removing paper with excellent performance can be efficiently prepared. At the same time, the present invention also performs detailed parameter optimization on each step involved, such as the particle size range of the molecular sieve, the doping ratio, the ultrasonic treatment conditions, the carbonization treatment conditions, etc. In addition, the present invention also takes into account the proportion of pulp, the details of the papermaking process and the subsequent pattern printing process, so that the prepared formaldehyde-removing paper has significant advantages in performance, appearance and application. DETAILED DESCRIPTION
[0019] Embodiment 1: A method for preparing formaldehyde-removing paper, the specific steps are as follows: (1) Select OMS-2 molecular sieve with a particle size of 10 nanometers and wet-mix it with activated carbon fiber raw material with a specific surface area of 1000 square meters / gram at a mass ratio of 10%. Treat it at an ultrasonic frequency of 40 kHz for 1 hour to form raw fiber doped with molecular sieve.
[0020] (2) The raw fiber doped with the molecular sieve was carbonized in a nitrogen atmosphere at a carbonization temperature of 800° C. for 2 hours to prepare activated carbon fibers containing the OMS-2 molecular sieve.
[0021] (3) The activated carbon fiber was immersed in a 0.1 mol / L silver nitrate aqueous solution for 24 hours and aged for 12 hours. The activated carbon fiber was then dried at 100°C and finally calcined at 300°C for 2 hours to obtain a formaldehyde degradation catalyst loaded with silver on the surface.
[0022] (4) Mix sulphate conifer pulp and bleached sulphate hardwood pulp in a mass ratio of 1:2 to form pulp, and add the above-mentioned formaldehyde degradation catalyst to the pulp in a mass ratio of 5%. Form paper sheets through a wet papermaking process, with a pressing pressure of 2 MPa, a drying temperature of 100°C, and a time of 10 minutes. Then, a sizing treatment is performed, and the glue used is polyvinyl alcohol, and the sizing amount is 5% of the paper weight. Then, a non-woven fabric coating treatment is performed, and the mass of the non-woven fabric is 10% of the paper weight. Finally, a calendering treatment is performed, with a pressure of 1 MPa and a calendering number of 2 times.
[0023] (5) The formaldehyde-removing paper is processed with pattern printing, and a beautiful pattern is printed by gravure printing.
[0024] The thickness of the prepared formaldehyde-removing paper is 0.3 mm and the weight is 120 g / m2. After testing, the formaldehyde-removing paper has excellent formaldehyde adsorption and degradation performance, and good physical properties such as softness and smoothness.
[0025] Comparative Example 1 The difference from the embodiment is that the OMS-2 molecular sieve is directly impregnated with a silver nitrate solution to prepare the formaldehyde degradation catalyst.
[0026] Comparative Example 2 The difference from Example 1 is that in step (1), no OMS-2 molecular sieve is added, and only activated carbon fiber raw material is used for carbonization treatment.
[0027] Comparative Example 3 The process is basically the same as Example 1, except that the addition ratio of the formaldehyde degradation catalyst in step (4) is 20%.
[0028] Characterization Formaldehyde adsorption and degradation performance characterization: Method: A dynamic formaldehyde adsorption test device was used to inject a certain amount of formaldehyde gas into a sealed test chamber, and then the prepared formaldehyde removal paper sample was placed in the test chamber. The formaldehyde adsorption degradation rate of the formaldehyde removal paper was calculated by regularly detecting the changes in the formaldehyde concentration in the chamber.
[0029] Data recording: record the formaldehyde concentration in the test chamber before and after placing the formaldehyde removal paper, as well as the formaldehyde concentration after 24 hours, and calculate the formaldehyde degradation rate.
[0030] Physical performance characterization: Softness: Use a paper softness tester to test, place the formaldehyde-free paper sample on the tester, test according to the tester's operating procedures, and record the test results. The softness test result is based on the instrument's reading, and the larger the value, the better the softness.
[0031] Smoothness: Use a paper smoothness tester to test, place the formaldehyde-free paper sample on the tester, test according to the tester's operating procedures, and record the test results. The smoothness test results are expressed in gloss units, and the larger the value, the higher the smoothness.
[0032] Thickness and weight: Use a thickness gauge to measure the thickness of the formaldehyde-free paper, and use a weight gauge to measure the weight of the formaldehyde-free paper. The thickness is expressed in millimeters, and the weight is expressed in grams per square meter.
[0033] Characterization data: Example 1: Formaldehyde adsorption and degradation performance: The initial formaldehyde concentration was 1.0 mg / m³. After placing the formaldehyde removal paper, the formaldehyde concentration was 0.09 mg / m³ 24 hours later, and the formaldehyde degradation rate was 91%.
[0034] Physical properties: softness is 86, smoothness is 92 gloss units, thickness is 0.3 mm, and weight is 121 g / m².
[0035] Comparative data: Comparative Example 1: Formaldehyde adsorption and degradation performance: The initial formaldehyde concentration was 1.0 mg / m³. After placing the formaldehyde removal paper, the formaldehyde concentration was 0.31 mg / m³ 24 hours later, and the formaldehyde degradation rate was 69%.
[0036] Physical properties: softness is 56, smoothness is 75 gloss units, thickness and weight are similar to those in Example 1.
[0037] Comparative Example 2: Formaldehyde adsorption and degradation performance: The initial formaldehyde concentration was 1.0 mg / m³. After placing the formaldehyde removal paper, the formaldehyde concentration was 0.44 mg / m³ 24 hours later, and the formaldehyde degradation rate was 56%.
[0038] Physical properties: softness is 84, smoothness is 88 gloss units, thickness and weight are similar to those in Example 1.
[0039] Comparative Example 3: Formaldehyde adsorption and degradation performance: the initial formaldehyde concentration was 1.0 mg / m³, the formaldehyde concentration was 0.18 mg / m³ 24 hours after placing the formaldehyde removal paper, and the formaldehyde degradation rate was 82%.
[0040] Physical properties: softness is 78, smoothness is 82 gloss units, thickness is 0.32 mm, and weight is 125 g / m². Compared with Example 1, the softness and smoothness are reduced, and the thickness and weight are slightly increased.
[0041] It can be seen from the above data that the formaldehyde removal paper of Example 1 performs well in formaldehyde adsorption degradation performance and physical properties. However, Comparative Examples 1, 2 and 3 all have varying degrees of reduction in formaldehyde degradation performance or physical properties. This proves the importance of the combination of OMS-2 molecular sieve and activated carbon fiber and silver loading treatment in the present invention to improving the performance of formaldehyde removal paper. At the same time, the effectiveness of the preparation method and parameter optimization provided by the present invention is also verified.
Claims
1. A method for preparing formaldehyde-removing paper, characterized in that: The following steps are included in sequence: (1) Nano-scale OMS-2 molecular sieves were doped into activated carbon fiber raw materials through wet mixing and ultrasound-assisted technology to form raw fiber doped with molecular sieves; (2) carbonizing the raw fiber doped with the molecular sieve to prepare activated carbon fiber containing the OMS-2 molecular sieve; (3) silver loading treatment is performed on the activated carbon fiber to obtain a formaldehyde degradation catalyst loaded with silver on the surface; (4) Add formaldehyde degradation catalyst to pulp and prepare formaldehyde-free paper through papermaking process.
2. The method for preparing formaldehyde-removing paper according to claim 1, characterized in that: The nano-scale OMS-2 molecular sieve in step (1) has a particle size range of 5-50 nanometers and is doped into the activated carbon fiber raw material at a mass ratio of 5%-20%; the specific surface area of the activated carbon fiber raw material is 500-1500 square meters / gram.
3. The method for preparing formaldehyde-removing paper according to claim 1 or 2, characterized in that: In the wet mixing and ultrasonic-assisted treatment in step (1), the frequency range of the ultrasonic treatment is 20-60 kHz, and the treatment time ranges from 30 minutes to 1.5 hours.
4. The method for preparing formaldehyde-removing paper according to claim 3, characterized in that: The carbonization treatment in step (2) is carried out in a nitrogen atmosphere, the carbonization temperature ranges from 700 to 900° C., and the carbonization time ranges from 1 to 3 hours.
5. The method for preparing formaldehyde-removing paper according to claim 4, characterized in that: The silver loading treatment in step (3) comprises: immersing the activated carbon fiber in an aqueous solution containing a silver active component at a concentration of 0.05-0.2 mol / L, the immersion time ranges from 12-36 hours, the aging time ranges from 6-24 hours, and then drying at 80-120°C, and finally calcining at 250-350°C, the calcination time ranges from 1-3 hours.
6. The method for preparing formaldehyde-removing paper according to claim 5, characterized in that: The aqueous solution containing the silver active component is one of silver nitrate, silver phosphate, silver carbonate or silver acetate.
7. The method for preparing formaldehyde-removing paper according to claim 5, characterized in that: The pulp in step (4) is prepared by mixing kraft softwood pulp and bleached kraft hardwood pulp in a mass ratio of 1:1 to 1:3; and the formaldehyde degradation catalyst is added to the pulp in a mass ratio of 1% to 10%.
8. The method for preparing formaldehyde-removing paper according to claim 6, characterized in that: The papermaking process in step (4) comprises: forming paper sheets by a wet papermaking process using a slurry containing a degradation catalyst; pressing the paper sheets at a pressure range of 1-3 MPa; drying the paper sheets at a temperature range of 90-110° C. for a time range of 5-15 minutes; applying a sizing agent using a polyvinyl alcohol or sodium carboxymethyl cellulose glue in an amount of 3%-7% of the paper weight; applying a non-woven fabric, the mass of the non-woven fabric being in a range of 5%-15% of the paper weight; and finally calendering the paper sheets at a pressure range of 0.5-1.5 MPa for 1-3 calendering cycles.
9. The method for preparing formaldehyde-removing paper according to claim 7, characterized in that: The method further includes printing a pattern on the formaldehyde-removing paper after the papermaking process in step (4), wherein the printing method includes gravure printing, flexographic printing or digital printing.
10. The method for preparing formaldehyde-removing paper according to claim 8, characterized in that: The thickness of the prepared formaldehyde-removing paper product is 0.1-0.5 mm, and the gram weight ranges from 80-200 g / m2.
Citation Information
Patent Citations
A solid-phase OMS-2 molecular sieve catalyst for formaldehyde purification at room temperature and its preparation method
CN111266129B